Ақпараттық-коммуникациялық технологиялар студенттердің рухани-адамгершілік құндылықтарөрісін байытудың құралы ретінде - Каирова, Б.К. (My University, 2016)
This article considers a problem about using information and communication technologies in educational system and how it helps to expand cognitive processes, social activity, self-dependence, desire to learn and improve personal qualities, in this way, the spiritual and moral sphere of youth becomes enriched.
Keywords: information and communication technologies; interactive methods of teaching; art therapy; review and analysis of video material; heuristic questions and conversation; bibliotherapy; values; spiritual and moral values